Iatrogenic dislocation of the lower wisdom tooth to the perimandibular space – a case report - Ambicki, Miłosz; Lewandowski, Bogumił (Journal of Stomatology, 2019)
Iatrogenic dislocation of the lower wisdom tooth to the bottom of the oral cavity and neck is a rare complication that may occur during surgical extraction, usually causing inflammation and abscesses, and therefore it requires specialist treatment in a hospital in the Department of Maxillo-Facial Surgery. The case described in this paper required surgical removal of the displaced tooth and evacuation of the abscess from the extraoral approach. The patient had uneventful perioperative course, no postoperative complications were observed, and the healing proceeded in a normal way. During three outpatient follow-ups carried out at intervals of one month, no abnormalities in healing were found.